ERRORS OF CENTRAL SULAWESI STUDENTS IN WRITING RECOUNT TEXT - Rifka Rahmita; Afrillia Anggreni (Universitas Muhammadiyah Makassar, 2023)
This research aimed to expose types and most frequent errors in recount writing of Central Sulawesi students in which focused on linguistics category taxonomy and limited on Morphology and Syntax. A descriptive qualitative and document analysis were employed in this research. The subjects of this research were 36 students of grade X MIPA 4 at SMA Negeri 1 Palu. The result of the research presents that there were 277 errors in students’ writing: 123 or 44.40% omission errors, 20 or 7.22% addition errors, 134 or 48.38% misformation errors, but there were no found misordering errors on the students’ writing. According to the percentage of errors occurence, the most frequent error was misformation errors. The students frequently misused the formations of pronoun, preposition, main verb, auxiliary verb be, copula be, auxiliary verb have, modal auxiliary, subject-verb agreement, and verb-and-verb construction. It implies that the students writing still presents many kinds of error in their writing and the teacher should discuss more about it.